Detection of soil pipes through remote sensing and electrical resistivity method: Insight from southern Western Ghats, India. (20th February 2021) - Joshi, Mayank; Prasobh, P.R.; Rajappan, S.; Rao, B. Padma; Gond, Alka; Misra, Anshuman; Eldhose, K.; Nandakumar, V.; Tomson, J.K.
Abstract: Every year, during the monsoon period (June–September), series of land subsidence incidences are reported from the Southern Western Ghats in India. These land subsidences occur primarily due to subsurface erosion, which leads to formation of soil pipes. These soil pipes are geo-morphologically an outcome of land degradation process that significantly influences the hill slope hydrology which makes the slopes vulnerable, and affects the human lives as well. However, detection of these subsurface pipes remains a serious challenge. Most of the previous studies are based on surface investigations, without considering the subsurface features. The present study aims to provide a more detailed account of these less-studied geomorphic features (soil pipes) using an integrated approach. The main purposes of the present study are to 1) describe the characteristic of the soil pipes and 2) to quantify the scale of piping activity; based on both surface and subsurface investigations in watershed scale. The remote sensing and GIS platform were used to delineate watershed boundary, identify geo morphological setup of the terrain, detailed landuse information and to bring out change in landuse, landcover pattern. The geomorphic mapping was carried out to identify the type of pipes, location of its inlet, outlet and other subsequent deformation features. The resistivity survey was done to map geometry of the pipe, piping network, subsurface lithology, and get the water table depth. The resistivity survey results indicate that the density of pipes are more than the estimated through surface mapping. Similarly, the length of the pipes is more than the mapped pipe through the surface mapping. The combined results suggest that the region is rich in these kinds of pipe features and may create hazard to the society residing in those areas. This study further underlined the importance of detailed study about soil piping phenomena to minimize its threat to human habitation and to provide specific recommendations to prevent the recurrence.